Imigrant — Uchodźca — Obcy? Nie-Polak jako Inny w wybranych dziełach kinematografii polskiej lat 2015–2021 - Wąsala, Piotr (Zagadnienia Rodzajów Literackich, 2022)
The article analyses the ways of presenting the Other — an immigrant, a refugee, a non-Pole — in selected works of Polish cinema from 2015 to 2021. The author examines films featuring foreigners in the leading (Never Gonna Snow Again by Małgorzata Szumowska) and supporting roles (The Sun, the Sun Blinded Me by Wilhelm and Anna Sasnal), as well as in the bit parts (Tower. A Bright Day by Jagoda Szelc). The article attempts to determine, describe, and compare the depictions of the Other. Moreover, the article seeks to establish an increased significance of these characters and incite the viewer to re-examine the entrenched connotations. Presenting the world through the eyes of a non-Pole and/or making their presence prominent within traditionally Polish-only spheres is a relatively new phenomenon within Polish cinema and, as such, calls for augmented analysis and interpretation that follows the spirit of transcultural studies. It is significant that the Other, as a character in Polish cinema, is becoming more and more independent and authentic; their depiction seems to have lost the oriental and caricatural features of the past and the Other often contrasts with the Polish figure. The presence of the Other as an empowered character symbolises the shift in perceiving Polish society as stereotypically homogenous.